2022
DOI: 10.3390/microorganisms10030641
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate Esters Metabolic Strain Gordonia sp. GZ-YC7, a Potential Soil Degrader for High Concentration Di-(2-ethylhexyl) Phthalate

Abstract: As commonly used chemical plasticizers in plastic products, phthalate esters have become a serious ubiquitous environmental pollutant, such as in soil of plastic film mulch culture. Microbial degradation or transformation was regarded as a suitable strategy to solve the phthalate esters pollution. Thus, a new phthalate esters degrading strain Gordonia sp. GZ-YC7 was isolated in this study, which exhibited the highest di-(2-ethylhexyl) phthalate degradation efficiency under 1000 mg/L and the strongest tolerance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…However, the plasticity of genomes and metabolic flexibility of representatives of the genus Gordonia make them interesting for both fundamental studies and practical applications. Gordonia strains are mainly known as degraders of alkanes [29][30][31], but among them there are also degraders of thiophenes [26,32], phthalates [33][34][35] and steroids [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…However, the plasticity of genomes and metabolic flexibility of representatives of the genus Gordonia make them interesting for both fundamental studies and practical applications. Gordonia strains are mainly known as degraders of alkanes [29][30][31], but among them there are also degraders of thiophenes [26,32], phthalates [33][34][35] and steroids [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Gordonia strains are interesting for application in biotechnologies of environmental purification as degraders of pollutants of different chemical structures, such as alkanes [11][12][13][14], aromatic hydrocarbons [15,16] and their derivatives [17,18], thiophenes [19][20][21], and phthalates [22][23][24][25][26]. The type strains of several Gordonia species were isolated from soils contaminated with thiophenes (G. amicalis [27]), tar (G. alkanivorans [28]), from automobile tires (G. polyisoprenivorans [29], G. westfalica [30]), oil-producing wells (G. paraffinivorans [31]), and activated sludge [23].…”
Section: Introductionmentioning
confidence: 99%
“…The strains Gordonia hongkongensis RL-LY01 [37] and Gordonia sp. GZ-YC7 [38] exhibit a strong potential for environmental bioremediation due to their ability to effectively degrade various phthalate esters or phthalic acid esters (PAEs). Hu et al (2022) reported that Gordonia sp.…”
Section: Introductionmentioning
confidence: 99%
“…GZ-YC7 [38] exhibit a strong potential for environmental bioremediation due to their ability to effectively degrade various phthalate esters or phthalic acid esters (PAEs). Hu et al (2022) reported that Gordonia sp. GZ-YC7 efficiently removed more than 45% of di-(2-ethylhexyl) phthalate with an initial concentration of 500 mg/kg within 5 days, even when soil microbial activity is typically inhibited at lower di-(2-ethylhexyl) phthalate (DEHP) concentrations.…”
Section: Introductionmentioning
confidence: 99%